EQUILIBRIUM STRUCTURES OF MINERAL AGGREGATES IN DEEP-SEATED LHERZOLITE NODULES - Zhabin A.G.; Gladkikh V.C. (My University, 1990)
The identification of equilibrium mineral assemblages in rocks is an important problem which can be solved not only by applying the principles of physical chemistry but also by observing the morphological characteristics of the mineral aggregates themselves. We have worked out a semi-quantitative method based on morphological characteristics which can help to determine the degree of equilibrium attained by the rock fabric. This method helps to evaluate what is most essential in the understanding of mineral paragenesis, namely, the synchroneity of crystallization of coexisting minerals. Based on the measured angles and the trace element concentration, it can be concluded that the coexisting orthopyroxene, clinopyroxene and olivine represent paragenetic equilibrium assemblages which crystallized in the mantle. This is supported by the equilibrium character of the grain-boundary framework and the trace element partitioning between minerals.